Major histocompatibility complex-associated resistance to infectious diseases: the case of bovine leukemia virus infection - Gutiérrez, Silvina Elena (2017)
The major histocompatibility complex (MHC) is a polymorphic gene cluster of about 150 genes, present in all vertebrates. Many of these genes contribute to immunity. Particularly, MHC‐encoded class I and class II molecules, which are typically highly polymorphic and polygenic, are central in defining the specificity of the adaptive immune response. Among the diversity of genes associated with disease resistance, MHC genes are particularly interesting as they are associated with resistance and susceptibility to a wide range of diseases, some of which produce important economic losses in livestock. Enzootic bovine leukosis is an infectious disease caused by the retrovirus bovine leukemia virus (BLV), with an important economic impact, mainly in dairy herds. In this chapter, MHC‐associated genetic resistance to BLV is revised. Certain alleles of the bovine MHC (BoLA) class II locus have been found strongly associated with resistance to viral dissemination. Genetic selection of resistant animals emerges as a natural strategy for the control of infectious diseases, especially when there is no other alternative of control or prevention, as vaccines. Founded on this knowledge, a BLV control program based on selection of genetically resistant cattle was designed. The proof of concept indicates that this strategy is feasible to implement in dairy herds.